Repeated exposure to methamphetamine, cocaine or morphine induces augmentation of dopamine release in rat mesocorticolimbic slice co-cultures. - Takayuki Nakagawa; Yuichi Suzuki; Kazuki Nagayasu; Maiko Kitaichi; Hisashi Shirakawa; Shuji Kaneko (PLoS ONE, 2011)
Repeated intermittent exposure to psychostimulants and morphine leads to progressive augmentation of its locomotor activating effects in rodents. Accumulating evidence suggests the critical involvement of the mesocorticolimbic dopaminergic neurons, which project from the ventral tegmental area to the nucleus accumbens and the medial prefrontal cortex, in the behavioral sensitization. Here, we examined the acute and chronic effects of psychostimulants and morphine on dopamine release in a reconstructed mesocorticolimbic system comprised of a rat triple organotypic slice co-culture of the ventral tegmental area, nucleus accumbens and medial prefrontal cortex regions. Tyrosine hydroxylase-positive cell bodies were localized in the ventral tegmental area, and their neurites projected to the nucleus accumbens and medial prefrontal cortex regions. Acute treatment with methamphetamine (0.1-1000 µM), cocaine (0.1-300 µM) or morphine (0.1-100 µM) for 30 min increased extracellular dopamine levels in a concentration-dependent manner, while 3,4-methylenedioxyamphetamine (0.1-1000 µM) had little effect. Following repeated exposure to methamphetamine (10 µM) for 30 min every day for 6 days, the dopamine release gradually increased during the 30-min treatment. The augmentation of dopamine release was maintained even after the withdrawal of methamphetamine for 7 days. Similar augmentation was observed by repeated exposure to cocaine (1-300 µM) or morphine (10 and 100 µM). Furthermore, methamphetamine-induced augmentation of dopamine release was prevented by an NMDA receptor antagonist, MK-801 (10 µM), and was not observed in double slice co-cultures that excluded the medial prefrontal cortex slice. These results suggest that repeated psychostimulant- or morphine-induced augmentation of dopamine release, i.e. dopaminergic sensitization, was reproduced in a rat triple organotypic slice co-cultures. In addition, the slice co-culture system revealed that the NMDA receptors and the medial prefrontal cortex play an essential role in the dopaminergic sensitization. This in vitro sensitization model provides a unique approach for studying mechanisms underlying behavioral sensitization to drugs of abuse.